Design and Evaluation of Gastro-Retentive Floating Tablets of Captopril - R. S.RADKE; S. B. DESHMUKH; P. S. JAGTAP; P. S. GANGANE; D. R. GODWANI (International Journal of Pharma and Bio Sciences, 2010)
In the present investigation, an attempt has been made to increase therapeutics efficacy, reduce frequency of administration and improve patient compliance by developing sustained release gastro retentive floating tablets of captopril using hydrocolloids like hydroxyl-propyl methylcellulose and Carbopol 934P by effervescent technique using direct compression method. The prepared tablets were evaluated in terms of their physical characteristics, in vitro release, buoyancy, buoyancy lag-time and swelling index. The results of the in vitro release studies showed that the optimized formulation sustained drug release for 24 h and tablets remained buoyant for more than 24 h. When these dissolution profiles were subjected to various kinetic release investigations and it was observed that the mechanism of drug release was diffusion controlled with a minor contribution from polymeric relaxation. It was found that optimized formulation showed no significant change in physical appearance, drug content, floatability and in vitro dissolution pattern after storage at 45 °C/75% RH for three months.